2018
DOI: 10.2514/1.j056576
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Flow Perturbation Spectra in Mach 4.5 Corner Separation Zone

Abstract: Characterization of the M 4.5 flow over a flat-plate model with a 30 deg compression ramp was performed with low-enthalpy (T 0 300 K) and high-enthalpy (T 0 800-1250 K) flow conditions for a wide range of unit Reynolds numbers (Re l 4 ⋅ 10 5 − 1 ⋅ 10 7 m −1). Three measurement techniques were employed to measure the frequency spectrum of flow perturbations: a high-frequency Shack-Hartmann wavefront sensor (aerooptical method), highfrequency PCB™ pressure sensors, and a laser differential interferometer. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A different approach for plasma-based control of a supersonic inlet was employed in [16,17] where the pulse-periodic arc plasma was used to control the SW reflection. Recently, several exper imental efforts were performed to control the flowfield within a compression surface configuration at higher Mach numbers, M = 4.5 and 7, by means of different electrical discharges, such as shallow cavity discharge [18], and DC discharge [19,20]. In the first case, there was found a significant modification in the spectra of flow perturbations in a corner separation zone.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach for plasma-based control of a supersonic inlet was employed in [16,17] where the pulse-periodic arc plasma was used to control the SW reflection. Recently, several exper imental efforts were performed to control the flowfield within a compression surface configuration at higher Mach numbers, M = 4.5 and 7, by means of different electrical discharges, such as shallow cavity discharge [18], and DC discharge [19,20]. In the first case, there was found a significant modification in the spectra of flow perturbations in a corner separation zone.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In a broad sense, this interaction of light with turbulent aerodynamic flows is called the aero-optics problem. [5][6][7][8][9] In the recent past there has been significant research into the aero-optics problem across a wide range of flow regimes including subsonic, [10][11][12][13][14][15] supersonic, 16,17 and hypersonic 18,19 flows.…”
Section: Introductionmentioning
confidence: 99%
“…In [13][14][15][16] and other publications, the plasma-based technique and the mechanisms of the plasma-flow interaction were examined in supersonic flow. It was found that the near-surface electric discharge is well applicable for the purposes of the modification of surface pressure distribution, flow field pattern, and shock wave formation.…”
Section: Introductionmentioning
confidence: 99%